“Light Cavalry” of Komsomol in Mid-1930s: a Change of Priorities - A. S. Anatoly (Научный диалог)
The activities of the youth movement of young controllers “light cavalry” in the mid-1930s are analyzed. On the basis of archival documents and publications of the 1930s, the features of the solution of new tasks in production by the “light cavalry”, the participation of detachments in the organization of the Stakhanov movement were revealed. The specificity of the work of special youth associations in railway transport, in rural areas is shown. It is revealed that thanks to the efforts of the “light cavalry” to organize the Stakhanov movement, persistent actions aimed at increasing the efficiency of industrial and transport enterprises, protecting collective farm crops and property, its solid creative potential is demonstrated. Particular attention is paid to the attempts of the “light cavalry” since 1934 to restructure the work, strengthening the implementation of educational functions and the exchange of experience. It is noted that by the end of the period under study, the activity of the “light cavalry” was more understood as a school for educating a new person. It is concluded that the widespread opposition to many undertakings of the members of the organization, coupled with a lack of material interest and a workload of other assignments, leveled the decisive attitude not only of many activists, but also of those who were called upon to follow their example.